Universal Benefits of BRI “Grow and Green” for Climate Resilience in Tanjung Perepat, Berau - Syam, Sufriady (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The Grow and Green program is an ecosystem restoration and environmental conservation activity that involves community entities and articulates land productivity through productive plants. The program, which has been running since 2023, is on the 28-hectare land of the Berkah Usaha Sejahtera Farmer Group (KT. BUS). BRI in collaboration with the Bakau Benefits Universal Foundation (BakauMU) gave trust to KT. BUS as the beneficiary, accompanied by Universitas Muhammadiyah Berau (UMBerau), to improve the quality of forest resources and provide alternative income. The program objective is to restore, preserve ecosystems and improve the community's economy through improving the quality of forest resources to strengthen climate resilience. The program framework uses a sustainability approach, planting pattern design, data collection techniques and intensified monitoring. The grow and green program is present as a solution to optimize preservation land in Tanjung Perepat through area governance efforts by maximizing the role and capacity of farmer groups, implementing low emission forest management practices and strengthening business governance as an inclusive economic investment. The Grow and Green program is a universal benefit in maintaining a balance between the environment and community welfare ecologically, economically, socially and culturally, and creating management effectiveness that contributes significantly to global climate resilience.